सोभियत संघको भाषानीतिमा राजनैतिक प्रभाव {Political Influence on the Language Policy of the Soviet Union} - Niroula, Tanka (Educational Journal, 2024)
प्रस्तुत लेख सोभियत संघको भाषानीतिलाई त्यहाँको राजनीतिले के कसरी र  के कस्तो प्रभाव पार्यो भन्ने विषयसँग सम्बन्धित छ । यस लेखमा भाषानीति भनेको के हो भन्ने विषयमा पनि चर्चा गरिएको छ । त्यसै गरी यस लेखमा सोभियत संघले आफ्नो अस्तित्वकाल (सन्.१९२२– १९९१) मा बहुजातीय र बहुभाषिक समाजलाई एकीकृत गर्न भाषालाई राजनैतिक साधनको रुपमा प्रयोग गर्यो भन्ने विश्लेषण पनि गरिएको छ । यसका साथै यस लेखमा सोभियत संघको केन्द्रीय नेतृत्वले कहिले बहुभाषिकतालाई आत्मसात् गर्यो भने कहिले रुसी भाषालाई रुसीकरण गरेर अन्य स्थानीय भाषालाई गौण बनायो भन्ने निधो पनि निकालिएको छ । संसारमा सोभियत संघले सर्वप्रथम भाषानीति बनाएको, लेनिनपूर्वका जार साही,लेनिन , स्टालिन र स्टालिनपछिको नेतृत्वले सोभियत संघको भाषानीति आफू अनुकूल तय गरेको,सोभियत संघको भाषानीतिलाई नै आधार बनाएर अन्य देशले आआफ्ना राष्ट्र र समाजका प्रकृति अनुकूलका भाषानीति बनाएको भन्ने विश्लेषण पनि यस लेखको मुख्य पाटो अन्तर्गत पर्छ । वास्तवमा सोभियत संघले तय गरेको भाषानीतिमा त्यहाँको राजनीतिले असरदार प्रभाव पार्यो भन्ने निष्कर्ष नै यस लेखको सार हो । अनुसन्धानको गुणात्मक ढाँचालाई आधार बनाएर तयार पारिएको यस लेखमा विषयवस्तुको प्रस्तुतिमा वर्णनात्मक र विश्लेषणात्मक प्रक्रिया अपनाइएको छ।{This article is related to how and to what extent politics influenced the language policy of the Soviet Union. It also discusses the concept of language policy itself. Furthermore, the article analyzes how the Soviet Union, during its existence (1922–1991), used language as a political tool to unify its multiethnic and multilingual society. Additionally, the article concludes that the central leadership of the Soviet Union sometimes embraced multilingualism, while at other times, it prioritized the Russian language through a process of Russification, thereby marginalizing other local languages. The article also explores how the Soviet Union was the first in the world to formulate a language policy, and how different leadership periods — from the Tsarist regime before Lenin, to Lenin, Stalin, and the post-Stalin era — shaped the Soviet language policy according to their political interests. Based on the Soviet model, other countries also developed their own language policies in alignment with the nature of their nations and societies. The core conclusion of this article is that the language policy formulated by the Soviet Union was heavily influenced by its political ideology and leadership. This article, prepared based on a qualitative research design, employs descriptive and analytical approaches in the presentation of the subject matter.}